Time response of FOPID controlled PV based cascaded landsman converter-inverter fed induction motor and electric drives applications - R. Pazhanimurugan; R. Bensraj; C.R. Balamurugan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Time Response enhancement utilizing photovoltaic based cascaded Landsman Converter (LC) structure is one of the soft strategies in the recent scenario. The prime function of a DC-DC Landsman converter is to optimize the output power of the photovoltaic array and reduce the output voltage ripples. This paper reveals the demonstration and simulation of the Cascaded Landsman Converter Inverter System (CLCIS) with a PV source. MATLAB Simulink-model for CLCIS has been created utilizing the components of Simulink and closed-loop examinations are performed with PI and Fractional-Order-PID (FOPID) Controllers. The present work deal with the comparison of transient and steady-state time responses of CLCIS with PI and FOPID controllers. The outcomes demonstrate that dynamic reaction is enhanced by utilizing FOPID controller.